Nurses’ views on medication administration system support for professional and safe medication administration - Santavirta, Jenni; Kuusisto, Anne; Saranto, Kaija; Suominen, Tarja; Asikainen, Paula (Finnish Journal of eHealth and eWelfare, 2020)
Safe medication administration is central part of nurses’ work. Safe medication has been studied trough medication errors, but there is less research information about supporting aspects of safe and professional medication administration. The purpose of this study is to describe nurses’ views of what supports safe and professional medication administration in the current medication administration system. Medication administration system stand for all organization’s structures and practices that supports or directs medication administration and any actions related to that. The study was conducted in one of Finland’s central hospitals. Data was collected with open-ended section and background questions of back translated Medication Administration System – Nurses Assessment Scale (MAS - NAS). Data was inductively analyzed using content analysis. Safe medication administration is supported with appropriate storing place, supplies available as needed, availability of extra information on medicines, usefulness and good usability of electronic system, availability of patient-specific information, opportunity to ensure medication, checkup practices and taking responsibility of own actions in medication administration. Cooperation and keeping up to date are supporting elements of professional medication administration. To support safe medication administration, it is managers’ responsibility to provide nursing staff appropriate storage facilities, supplies, and facilities to ensure medication information is available and medication verification is possible. Checkup practices should be used and ensure everyone knows their medication responsibilities. The electronic system’s good usability and usefulness for nurses is key factor of safe medication administration. Professional medication administration confirms by information disseminating and superiors encourage to cooperation, education, and to active knowledge search.